The Effects of Academic Qualifications, Managerial Capabilities, and Perceived Organizational Support on Emotional Exhaustion and Their Implications for Work Productivity: A Study at Sunan Kudus Islamic Hospital - Aditya Angger Wibowo (Digital Innovation : International Journal of Management, 2026)
This study aims to investigate the influence of academic qualifications, managerial capabilities, and Perceived Organizational Support (POS) on emotional exhaustion and its implications for employee productivity at Sunan Kudus Islamic Hospital. Using a quantitative approach, data were collected via a questionnaire from 138 respondents. Instrument evaluation procedures were conducted through validity and reliability tests, while hypothesis testing was analyzed using Structural Equation Modeling (SEM). The findings reveal that academic qualifications and POS have a significant negative effect on emotional exhaustion, indicating that increased intellectual competence and strong organizational support are effective in reducing staff emotional exhaustion. Conversely, managerial capabilities were found to have no significant influence on emotional exhaustion. In the context of performance, the analysis results show that academic qualifications, managerial capabilities, and POS have a partial, positive, and significant effect on work productivity. Practically, this study suggests that hospital management prioritize human capital development and the strengthening of a supportive organizational climate to mitigate emotional exhaustion while accelerating operational efficiency in a sustainable manner.